Pemanfaatan Plaform Canva sebagai Media Pembelajaran Interaktif terhadap Peningkatan Kreativitas Digital - Ahla Syafana; Cahya Ranis Sholihatun Fitrah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Learning activities based on conventional printed media lacking attractive visual elements tend to cause student boredom and hinder their progress in digital technology. Departing from this issue, the purpose of this study, titled "Pemanfaatan Platform Canva Sebagai Media Pembelajaran Interaktif Terhadap Peningkatan Kreativitas Digital", is to evaluate how effectively Canva serves as an interactive learning tool. It is expected that the learning process will enhance students' visual communication skills and provide educators with tangible workload efficiency in compiling learning materials. In this study, a literature review was used to collect and synthesize credible secondary data from various scientific articles published over the last five years. Data analysis was conducted using a thorough content analysis. The analysis results indicate that the utilization of Canva enables a dynamic, concrete classroom atmosphere that captures students' attention. The availability of ready-to-use templates significantly helps teachers save time and energy when designing interactive media. Although its implementation faces infrastructure challenges and limited digital competence, utilizing the free features of Canva for Education, Bring Your Own Device (BYOD) policies, and project-based learning are tactical ways to overcome these problems. According to this study, Canva is a practical solution for building digital skills in the 21st century.